2023
DOI: 10.1177/21582440231188022
|View full text |Cite
|
Sign up to set email alerts
|

Factors of Women Entrepreneurship in Egypt: A Qualitative Perspective

Ashraf Borham,
Rosfizah Binti Md Taib,
Gyanendra Singh Sisodia
et al.

Abstract: Extensive studies related to women’s entrepreneurial motivation are available in the western context, however, only a few studies are found focused on factors that motivate Egyptian women to engage in entrepreneurial activities. The study explores in-depth the motivations behind female entrepreneurs’ efforts to establish business ventures in Egypt. It analyses the influence of macrosocial realities and cultural values on the motivation for entrepreneurship. The finding demonstrates how post materialism factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
1
0
0
Order By: Relevance
“…A similar result was also found in Malaysia where rural women organizing their businesses were driven by attraction factors such as the desire for success, self-proof, self-confidence, tendency to be independent and having income to help take care of the family (Yap et al, 2023). In Egypt, the results of research (Borham et al, 2023) showed that the decision to start doing business covers a wide range of intrinsic motivations: internal motivations include the desire for independence and personal freedom, self-actualization, employing knowledge and benefiting from personal creative energies.…”
Section: Entrepreneurial Motivessupporting
confidence: 68%
“…A similar result was also found in Malaysia where rural women organizing their businesses were driven by attraction factors such as the desire for success, self-proof, self-confidence, tendency to be independent and having income to help take care of the family (Yap et al, 2023). In Egypt, the results of research (Borham et al, 2023) showed that the decision to start doing business covers a wide range of intrinsic motivations: internal motivations include the desire for independence and personal freedom, self-actualization, employing knowledge and benefiting from personal creative energies.…”
Section: Entrepreneurial Motivessupporting
confidence: 68%